A Novel Coupled Resonator Photonic Crystal Design in Lithium Niobate for Electrooptic Applications. (18th November 2015) - Ozturk, Birol; Yavuzcetin, Ozgur; Sridhar, Srinivas
Abstract : High-aspect-ratio photonic crystal air-hole fabrication on bulk Lithium Niobate (LN) substrates is extremely difficult due to its inherent resistance to etching, resulting in conical structures and high insertion losses. Here, we propose a novel coupled resonator photonic crystal (CRPC) design, combining a coupled resonator approach with that of Bragg gratings. CRPC design parameters were optimized by analytical calculations and FDTD simulations. CRPC structures with optimized parameters were fabricated and electrooptically tested on bulk LN annealed proton exchange waveguides. Low insertion loss and large electrooptic effect were observed with the fabricated devices, making the CRPC design a promising structure for electrooptic device applications.